THE EFFECTS OF WEIGHT LOSS METHODS IN EDUCATIONAL COMBAT SPORTS AND MARTIAL ARTS - Koca, Feyzullah; İmamoğlu, Osman; Türkmen, Mehmet (Acta Scientiae et Intellectus, 2024)
In this study, the effects of the weight loss methods on the students in the Combat sports and Martial Arts field were investigated. Sport Weight Loss Methods and Effects Scale were filled by a total of 208 university students who received sports education. Mann Whitney U and Kruskal Wallis tests were performed statistically. According to this study, while falling to the weight of the competition, 3% of their body weights and 2.91% of women have fallen. There was a statistically significant difference in fluid loss, physiological and psychological sub-dimensions of the scale according to the sex (p <0, 05 and p <0,001). Significant differences were found in relation to diet, ergogenic, physiological and psychological sub-dimensions according to the branches (p <0.05 and p <0.001). As a result, the students who played sports were generally affected by diet. While male students were more affected by fluid loss than female athletes, they were less affected by physiological and psychological care. A more comprehensive scale should be developed to determine weight loss methods in the elite level Combat sports and Martial Arts athletes. In addition, nutrition support should be provided.